Anonymous
Anonymous asked in Science & MathematicsMathematics · 1 decade ago

(x-1)^log(x-1)=100(x-1) How do you solve this?

1 Answer

Relevance
  • 1 decade ago
    Best Answer

    (x-1)^log(x-1)=100(x-1)

    Log both sides

    log(x-1)*log(x-1) = log(100(x-1))

    log(x-1)*log(x-1) = log100 + log(x-1)

    2log(x-1) = 2 + log(x-1)

    2log(x-1) - log(x-1) = 2

    log(x-1) = 2

    log(x-1) = 2, which can be written as

    10^2 = x-1

    100 = x-1

    x= 101

    Notes: log(xy) = logx + logy

Still have questions? Get your answers by asking now.